If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-4x + 1) = -33 Reorder the terms: 3(1 + -4x) = -33 (1 * 3 + -4x * 3) = -33 (3 + -12x) = -33 Solving 3 + -12x = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -12x = -33 + -3 Combine like terms: 3 + -3 = 0 0 + -12x = -33 + -3 -12x = -33 + -3 Combine like terms: -33 + -3 = -36 -12x = -36 Divide each side by '-12'. x = 3 Simplifying x = 3
| 118=159-x | | ab-2=bc-9 | | 36x^2-5x-1=0 | | 6y+12=9y | | 5-3x=5x+11 | | 90=-y+176 | | -124+3x=40-x | | 3x^2-20=11x | | 3(4x+1)=-33 | | -u+76=189 | | 12y-16=4y | | 0.40x=425000 | | 22=10c-8 | | 38-v=262 | | 2y-15=5 | | 8(2x-1)-4x=-116 | | 20+6(a-2)=5(a+3) | | 60y+30x=1950 | | 3x-22=-8x | | 10-2w=8 | | (p+7)(p+7)+(7-n)(7-n)=98 | | 2=-y+192 | | 2d-f=3 | | (p+7)2+(7-n)2=98 | | -22-7x=10-9x | | 24=3(2x-4) | | 2=-y+92 | | 2x+14=113 | | 214=-x+58 | | 30x+8=8x-124 | | 15x+12=-5x-12 | | 7(x-4)-2(x-8)=4(x-9)+6 |